Does the Level of Pedicle Subtraction Osteotomy Affect the Surgical Outcomes in Ankylosing Spondylitis-Related Thoracolumbar Kyphosis With the Same Curve Pattern?. Issue 7 (September 2022) - Tang, Zou-li; Qian, Bang-ping; Qiu, Yong; Liu, Zhuo-jie; Zhao, Shi-zhou; Huang, Ji-chen
Study Design: A retrospective study. Objective: To investigate the effect of pedicle subtraction osteotomy (PSO) level on the surgical outcomes in ankylosing spondylitis-related thoracolumbar kyphosis with the same curve pattern. Methods: ankylosing spondylitis (AS) patients with thoracolumbar kyphosis, who underwent 1-level lumbar PSO between March 2006 and June 2017, were retrospectively reviewed. Criteria for curve-matched thoracolumbar kyphosis were: (1) have same level of preoperative apex (pre-apex); (2) have similar global kyphosis (GK, the angle between the superior/inferior endplate of the maximally tilted upper and lower end vertebra) (the difference of GK less than 15˚). The radiographic parameters measured were sagittal vertical axis (SVA, the horizontal distance between the C7 plumb line and the posterosuperior corner of the S1), GK, thoracic kyphosis (TK, the angle between the T5 superior endplate and the T12 inferior endplate), lumbar lordosis (LL, the angle between the L1 and S1 superior endplate), sacral slope (SS, the angle between the sacral endplate and the horizontal line), pelvic tilt (PT, the angle between the vertical and the line joining the midpoint of the sacral plate and hip axis), and pelvic incidence (PI, the angle between the line vertical to the superior margin of S1 and the line connecting the sacral plate midpoint with the hip joint axis). All of these parameters and health-related quality of life (HRQoL, evaluated by preoperative and the last follow-up questionnaires including ODI and VAS) scores were collected before surgery and at the last follow-up. According to their osteotomy level, patients were devided into 2 sub-groups (L1 group and L2 group), and differences of these mentioned parameters between 2 groups were compared. Results: 26 curve-matched patients were recruited with a mean follow-up of 37.2 months. All patients improved significantly after surgery in HRQoL scores (VAS 1.6 vs 5.4, P < 0.001; ODI 11.9 vs 26.4, P < 0.001). Except for TK and PI, those radiographic parameters were also observed to be significantly changed after surgery. Compared to L2 group, PSO at L1 may have larger correction of TK (ΔTK -6.8 vs -0.3°, P = 0.164), PI (ΔPI -7.4 vs -0.7°, P = 0.364) and smaller correction of SVA (ΔSVA -105.3 vs -128.5 mm, P = 0.096), LL (ΔLL -31.1 vs -43.0°, P = 0.307) and SS (ΔSS 6.9 vs 12.2°, P = 0.279) but had no statistical significance. Conclusion: The results of this investigation showed that in AS-related thoracolumbar kyphosis patients with the same curve pattern, the different levels of osteotomy had little effect on the improvement of surgical outcomes. However, osteotomy at L2 is more likely to obtain a larger correction of SVA compared to osteotomy at L1.